2003
DOI: 10.1056/nejmoa030204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Food Intake in Obese Subjects by Peptide YY3–36

Abstract: We found that obese subjects were not resistant to the anorectic effects of PYY. Endogenous PYY levels were low in the obese subjects, suggesting that PYY deficiency may contribute to the pathogenesis of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
1,073
13
33

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,449 publications
(1,173 citation statements)
references
References 25 publications
54
1,073
13
33
Order By: Relevance
“…A reduction in plasma ghrelin in the obese A y /a mouse is consistent with the low plasma ghrelin found in obese humans. [37][38][39] The reduction in Arc NPY mRNA expression in obese A y /a mice may contribute to their increased linear growth. Our observation is in contrast to a previous study of obese A y /a mice of a comparable age and body weight that used similar techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in plasma ghrelin in the obese A y /a mouse is consistent with the low plasma ghrelin found in obese humans. [37][38][39] The reduction in Arc NPY mRNA expression in obese A y /a mice may contribute to their increased linear growth. Our observation is in contrast to a previous study of obese A y /a mice of a comparable age and body weight that used similar techniques.…”
Section: Discussionmentioning
confidence: 99%
“…CCK analysis used Phoenix Peptidese RIA (RK-069-04) for CCK octapeptide (CCK [26][27][28][29][30][31][32][33]. The standard RIA protocol was applied but without extraction of the peptides before the assay.…”
Section: Clinical Indicesmentioning
confidence: 99%
“…7 Studies in humans showed that peripheral infusion of postprandial level of PYY into normal and obese subjects decreased the caloric intake at a buffet meal by over 30% in both groups. 7,17 The fasting PYY levels and postprandial PYY release were lower in obese compared to lean individuals. 17 Recently, 101 patients with severe early-onset obesity in the UK were screened for mutations in the PYY and the Y2R genes.…”
Section: Introductionmentioning
confidence: 97%
“…7,17 The fasting PYY levels and postprandial PYY release were lower in obese compared to lean individuals. 17 Recently, 101 patients with severe early-onset obesity in the UK were screened for mutations in the PYY and the Y2R genes. 18 Two PYY SNPs common among both obese and control individuals, and in linkage disequilibrium (LD) with each other, were identified, one being Arg72Thr.…”
Section: Introductionmentioning
confidence: 97%